PERAN POSITIVE EMOTION SEBAGAI MEDIATOR HEDONIC SHOPPING DAN SHOPPING LIFESTYLE TERHADAP IMPULSE BUYING DI LAZADA - Nurlinda, R.A; Christina, Desi (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- The purpose of this research to determine whether the Hedonic Shopping and Shopping Lifestyle directly influences Positive Emotion, whether Hedonic Shopping, Shopping Lifestyle and Impulse buying directly influence Impulse buying and whether positive Emotion is proven as an intervening variable between Hedonic Shopping and Shopping Lifestyle on Impulse buying in Lazada. Design/methodology/approach- The independent variable consists of Hedonic Shopping and Shopping Lifestyle, the dependent variable is Impulse buying and the mediator variable is Positive Emotion. The sampling technique uses purposive sampling and the sample used is 160 respondents. Analysis of the data in this study used path analysis.Findings- The results of this study indicate that Hedonic Shopping has a direct effect on Positive Emotion, while Shopping Lifestyle has no direct effect on Positive Emotion. The results also showed that Hedonic Shopping, Shopping Lifestyle, and Positive Emotion had a direct influence on Impulse buying and Positive Emotion succeeded in becoming an intervening variable between Hedonic Shopping and impulse buying but was not proven as an intervening variable between shopping lifestyle and Impulse buying.Keywords: Impulse buying, Positive Emotion, Lifestyle Shopping, Hedonic Shopping